THE IMPORTANCE AND FEATURES OF TEACHING STUDENTS MOTHER LANGUAGE - Boboyev Yusuf Beknazarovich (American Journals, 2024)
Language is a fundamental aspect of human communication and identity. Teaching students their mother tongue plays a crucial role in cognitive development, cultural preservation, and academic success. This article explores the importance of mother tongue teaching and highlights the key features that contribute to effective language learning outcomes.
Keywords: Mother tongue, Critical thinking, identity, Linguistic competence, cognitive abilities.